Assessment of Digital Literacy Levels and Their Impact on E-Governance Adoption in Nepal - Maharjan, Shyam; Mahato, Ram Babu (Journal of Kathmandu BernHardt College, 2025)
This research aims to emphasize the need for digital literacy skills for the effective usage of e-governance practices adopted in Nepal. It involves the analysis of the digital divide generated between rural and urban citizens. The research relies on a mixed method, which involves both quantitative as well as qualitative research methods. It is applied to recognize the gap created regarding digital literacy skills, which further influences the usage/acceptance of e-governance practices. The study concludes that though citizens exhibit great confidence in computer and electronic communication utilization, they show very low levels of actual use of e-governance. The main challenges to achieving digital literacy include a lack of access to computerized devices and infrastructure, in addition to socio-economic inequalities, especially among rural residents. Another aspect that this study emphasizes as very significant to citizens' satisfaction in using e-governance includes internet connectivity reliability. Although a great deal of effort has been made in various government initiatives, including the use of e-governance, which enables citizens to apply for citizenship and also pay taxes, the absence of this basic digital literacy skill among the citizenry still continues to influence service delivery. Future studies should look at the relationship of socio-demographic factors on digital literacy, evaluate the efficiency of digital literacy initiatives, and also place emphasis on creating friendly e-governance platforms that suit all different groups of people.